Monitoring of small ice caps as indicators of the Antarctic Peninsula region climate change - Glotov, V. M.; Kovalenok, S. B.; Milinevsky, G. P.; Nakalov, E. F.; Fulitka, Yu. V. (Ukrainian Antarctic Journal, 2003)
The continuous geomorphology survey of the ice caps of the small islands in the Antarctic Peninsula region is concerned. The changes of the size, shape and edge location of ice caps of Argentina Island archipelago permit to use the geodetic survey data of the caps in studying the regional climate variability. The paper is based on historical data of the Galindez Island ice cap observation. The data of fifty years meteorological observations and tide data at Faraday/Vernadsky station, longer-term variability in sea-ice extent/thickness, monitoring of the ozone layer and UV energy flow, hydrology measurements provided at Vernadsky, the upper atmosphere change measurements over Antarctica, are the additional sources for the climate pattern of Antarctic Peninsula. The geodesy survey technology for the small island ice caps investigation in the Vernadsky station region is presented. The expected coordinates accuracy is calculated. It emphasizes the expediency of the reflection of glacier close parts in the vertical section. The Vernadsky station region geodetic survey data obtained during 2002 season are discussed.